Development of Miniaturized Satellite Technology for Global Environmental Monitoring - Bouyea Jonathan; Uwe Barroso; Amina Intes (Yayasan Adra Karima Hubbi, 2024)
Research Background: Global environmental monitoring is becoming increasingly important in an effort to maintain the balance of the earth's ecosystems. However, the limitations of conventional technology often become an obstacle in obtaining accurate and timely data. Research Objectives: This study aims to develop miniaturized satellite technology that can be used for global environmental monitoring effectively and efficiently. Research Methods: In this study, we analyzed existing miniaturized satellite technology and identified shortcomings and potential for further development. In addition, we conducted simulations and field trials to validate the performance of the developed technology. Research Results: The developed miniaturized satellite technology is capable of providing global environmental monitoring data with high accuracy and in a relatively short time. In addition, this technology also has the potential to be integrated with other monitoring systems. Research Conclusion: The development of miniaturized satellite technology has great potential in improving the effectiveness and efficiency of global environmental monitoring. With this technology, it is expected to make a significant contribution to efforts to preserve the earth's environment